Phosphorus forms by depth in sediments from the Qu’Appelle lakes, Saskatchewan, Canada - Wauchope-Thompson, Michelle S.; Cade-Menun, Barbara J.; Baulch, Helen M. (Frontiers in Environmental Science, 2022)
Understanding sediment phosphorus (P) compounds is essential to managing P in lake sediments because P speciation will determine bioavailability and reactivity. Little is known about organic P (Po) in hardwater lakes in the North American Great Plains, or the role of metals in Po cycling. Sediment cores (0–12 cm deep) collected from four lakes from the Qu’Appelle chain in Saskatchewan, Canada, were sectioned by depth and analyzed by solution P nuclear magnetic resonance spectroscopy to characterize P forms. Concentrations and pools of calcium (Ca), magnesium (Mg), iron (Fe), manganese (Mn), and aluminum (Al) were also determined. A range of P compounds was detected with significant interactions between lakes and depth for orthophosphate, phytate and DNA, and significant differences among lakes or with depth for polyphosphates and phosphonates. The main class of Po compounds identified in all lakes was orthophosphate diesters, including phospholipids and DNA, typical of living biota, suggesting that P immobilized by microbes and algae is an important pool in the sediments of these lakes. There were significant differences in metal concentrations among the lakes. In three lakes, Ca concentrations were high, and P was tightly bound with Ca compounds of low solubility. In the fourth lake, which had lower Ca concentrations, P appeared to be loosely bound to Al and Fe compounds. Our study indicates that there were significant differences in P compounds and the factors controlling their cycling among these four lakes in the same chain, which has implications for P management and water quality control.